EFEKTIFITAS EKSTRAK DAUN SUKUN HASIL PEREBUSAN TERHADAP PERTUMBUHAN KOLONI BAKTERI STREPTOCOCCUS MUTANS - Sariyem Sariyem; Sadimin Sadimin; Lanny Sunarjo; Makhyatun Haniyati (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2015)
TITLEEffectiveness of breadfruit leaf extract water stew to colony growth of Streptococcus mutansABSTRACTBreadfruit leaf flavonoid compounds useful as antimicrobial function kill or inhibit the growth of microorganisms. Breadfruit leaves also contain other compounds, namely saponins, polyphenols, tannins, hydrocyanic acid, acetylcholine, riboflavin, and phenols The aim of research was effectiveness results boiling breadfruit leaf extract on growth colony of bacteria Streptococcus mutans.This type of research used experimental method or experimental. In this research study is the growth of Streptococcus mutans bacteria colony before and after given the results boiling breadfruit leaf extract at a concentration of 10%, 20%, 40%, 60%. The design of the research is a pre-test-post-test with control group. In this research used two repetitions.The results of the research show that breadfruit leaf extract effectively inhibits the growth of bacterial colonies of Streptococcus mutans. Results boiling breadfruit leaf extract at a concentration of 60% of the most effective at inhibiting the growth of Streptococcus mutans bacteria colony than the concentration of 10%, 20%, 40%. Chemical compounds contained in the leaves of breadfruit namely polyphenols which have properties as an antimicrobial against bacteria and fungi. Not only that, the breadfruit leaf also contains flavonoids that have powerful antimicrobial properties. An antimicrobial agent serves to kill or inhibit the growth of microorganisms. Flavonoids are polyphenolic compounds that have chemical properties that are slightly acidic phenols that can be dissolved in alkaline. Flavonoids are also contains hydroxyl groups that are generally soluble in polar solvents such as ethanol, methanol, butanol, acetone, and water. Key words : Breadfruit Leaf Extract, Streptococcus mutans